Analisis Pengaruh Pendanaan pada Koperasi Simpan Pinjam terhadap SHU di Kota Jakarta Barat Berdasarkan Aplikasi Online Data System Kementerian Koperasi dan UKM Periode Tahun 2022 - Ikhsan, Dkk, Sugiyanto (Coopetition : Jurnal Ilmiah Manajemen, 2025)
A cooperative is a form of economic organization that is owned and operated by its members to achieve common goals where the members have similar goals and economic interests. One reflection of the cooperative's success in achieving its goals can be seen from the SHU produced. The importance of SHU for cooperatives is not just a number in a financial report, but is an indicator of the cooperative's success in achieving its goals. This research aims to analyze the influence of funding sources consisting of own capital and loan capital on the ability of cooperatives to produce SHU at Credit Unions in West Jakarta City for 2022. This research uses quantitative research methods with multiple linear regression analysis. The total data sample are 44 credit unions that carry out and report RAT from 210 active cooperatives in West Jakarta City. Data source comes from the Online Data System (ODS) application of the Ministry of Cooperatives and SMEs. The research results show that simultaneously (together) Own Capital (X1) and Loan Capital (X2) have a positive effect with a contribution of 0.306 or 30.6% to the acquisition of SHU (Y). However, partially Own Capital has a more significant influence on SHU acquisition compared to Loan Capital. Increasing the own capital can be done by inviting cooperative members to actively pay and/or increase the amount of principal savings and mandatory savings as well as inviting outside members to join the cooperative in order to increase the amount of their own capital in the cooperative. Keywords: Credit Union, Funding, Own Capital, Loan Capital, SHU